The Myth of Value Free Counseling John F. Kegley. - Kegley, John F. (Distributed by ERIC Clearinghouse, 1975)
A counselor's values are inherent in all that he does with a client, ranging from selection of the counseling modality to the decision to terminate facilitative intervention. Value-free counseling is a myth, and recognition of this fact is the first step in arriving at a clear conception of what counseling can, or should, be. A counselor can be considered an advocate for what one can become. In this sense, counseling is a political, value-laden process to create tolerant personalities and safeguard human rights. Whatever means and modalities are employed in counseling to facilitate the development of the tolerant personality, the process must be a liberating one that releases the mind and emotions from ignorance, prejudice, partisanship or superstition, that emancipates the will, stimulates the imagination, broadens the sympathies, generates empathy and makes the client a citizen of the world. (Author/PC)
ERIC Document Number: ED109556.
ERIC Note: Paper presented at the Annual Meeting of the American Personnel and Guidance Association (31st, New York, New York, March 23-26, 1975).
Keywords: Behavior Change.; Civil Liberties.; Communication (Thought Transfer); Counseling.; Humanism.; Moral Values.; Personality.; Self Actualization.; Speeches.; Therapeutic Environment.; Values.